On connection of variations between hard cosmic ray flux, temperature and cardiovascular diseases in Vilnius and sunspot number during 2001–2012 - Styro, Dmitrijus; Usovaite, Ana (Journal of Environmental Engineering and Landscape Management, 2015)
The connection has been found between the course of cardiovascular diseases (CVD) and the hard cosmic ray flux (HCRF) near the ground surface in Vilnius. The course of air temperature and number of sunspot was simultaneously considered. The investigation was carried out for the average annual and average monthly values in the period of solar cycle 2001–2012. The course of average annual data is most identical for HCRF and number of sunspot: whereas, it significantly differs from CVD and temperature course. The stable connection between a course of average monthly values of HCRF and CVD is found. Such a connection for temperature and CVD had a negative correlation with coefficient of correlation –0.9. A rather weak correlation was between the change in the number of sunspots another characteristics. Values of correlation coefficient between them were less than 0.4 during all of the solar cycle2001–2012. The exception had taken place at the maximum solar activity, i. e. in 2001 and 2012 when values of correlation coefficient exceeded 0.5. For the short-term prognosis of CVD leaps exceeding average monthly value by 10%in 1–3 days after HCRF decrease according to the proposed criterion, the high efficiency of the results 68–79% was obtained. The variation of sunspot number isn’t connected with these data. A short-term connection between the change in air temperature, the change in the sunspot number and CVD leaps has not been found. The human factor has an additional influence on CVD leaps, which was considered in these studies.